Gender Analysis of Santri’s Mental Health in Islamic Boarding Schools - Azizatul Hamidiyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Mental health is a health issue that is often ignored. In fact, 1 in 3 adolescent in Indonesia experience mental health problems. Neglect is caused by unawareness of one's condition. Not to mention the problem of negative stigma in people with mental disorders. The purpose of this study was to determine the relationship between gender and mental health of students in Islamic boarding schools. This research method was quantitative with a cross-sectional design. The number of samples in this study was 357 male and female santri in Islamic boarding schools. The sampling technique used proportional random sampling. Data collection was carried out using the Strength and Difficulties Questionnaire (SDQ) with 25 questions referring to the technical instructions for health screening and periodic examinations of school-age children and adolescents. Data analysis was carried out using the chi square test. The results of the study showed that female santri had greater mental health problems, namely in the abnormal category, higher than male santri. The results of the chi square test showed a Pvalue <0.05, meaning that there is a relationship between gender and mental health on the results of the SDQ difficulties, both in terms of emotional symptoms (<0.001), behavioral problems (0.031), hyperactivity (<0.001) and peers (<0.001) and cumulatively (0.001). However, there is no relationship between gender and mental health on the results of the SDQ strength (0.074).